The Role of Strategic Human Resources Management, Knowledge Management, and Innovation Capability on Innovation Performance in Pharmaceutical Company - Gerald Kevin Bonifacius H. (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
According to resources-based view, firm should manage resources strategically to create innovation for achieving competitive advantages. Human resources is one of the resources of the firm should be managed strategically. This study examines the role of knowledge management and innovation capability in the relationship between strategic human resources management (SHRM) and innovation performance. For this purpose an empirical research is conducted to analyze data from Indonesian pharmaceutical firms. The result indicates that SHRM practices are positively related to innovation performance directly and through innovation capability.